A Short History of K-12 Public School Spending in British Columbia, 1970-2020 - Ellis, Jason (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
This article looks at fifty years’ worth (1970-2020) of public K-12 education expenditure data from the Canadian province of British Columbia. It asks if spending has increased or decreased in this period and examines the causes and correlates of spending changes. Previous research has tended to assume that spending has decreased during this “neoliberal” period. However, historical and empirical research in this article gives a much different picture. K-12 public education spending in British Columbia – adjusted for inflation – is 250 percent higher in 2020 than it was in 1970. Meanwhile, enrolment in 2020 is only 110 percent of 1970 enrolment. The main cause of spending growth is increase in the number of teachers the system employs, which depended in no small part on the British Columbia Teachers’ Federation (BCTF)’s successful attempts to negotiate class size and composition rules. Other causes of spending growth are provincial and district spending priorities. Successive provincial governments have tried to rein in education spending by legislating cost controls on district spending and teacher contracts but have seldom achieved reductions for long. Spending increases and attempts at cost control are at best only linked partially to governing party ideology, with right-wing and left-wing provincial governments both initiating years of increases and cutbacks. More empirical research is needed, especially into spending’s effects on educational equity and quality, to complete the picture of education finance in British Columbia.